Pengaruh Environmental, Social, dan Governance Disclosure Score terhadap Nilai Perusahaan Subsektor Perbankan Periode 2022-2024 - Nahdiatuz Zahra; Divianto Divianto; Agung Anggoro Seto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to examine the effect of EDS, SDS, and GDS on company value in the banking subsector listed on the Indonesia Stock Exchange during the 2022-2024 period. This study uses a quantitative method with a descriptive approach. The study population is banking subsector companies listed on the Indonesia Stock Exchange, with a sampling technique using purposive sampling resulting in 9 banking companies as research samples for three years of observation, namely 2022-2024. The data used are secondary data sourced from the company's annual report and Bloomberg. Data analysis was carried out using the panel data regression method. The results show that partially EDS has a significant effect on company value with a probability value of 0.0850. Meanwhile, SDS does not have a significant effect on company value with a probability value of 0.3655. GDS also does not show a significant effect on company value, with a probability value of 0.3325. Simultaneously, EDS, SDS, and GDS do not have a significant effect on company value, as indicated by the Prob (F-statistic) value of 0.174333.